2020
DOI: 10.9734/cjast/2020/v39i130482
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence Studies for Anaerobic Germination Traits in Rice (Oryza sativa L.)

Abstract: The present investigation was carried out to study the inherent genetic diversity of 107 rice genotypes towards development of rice varieties with tolerance for germination under anaerobic conditions for use in wet direct seeded rice cultivation system. The diversity was evaluated using multivariate analysis technique of Mahalanobis D2. The 107 rice genotypes studied were grouped into nine clusters. Twenty nine genotypes were grouped in cluster II followed by 27, 22, 10, 11 and 5 genotypes each in clusters I, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
(11 reference statements)
3
3
0
Order By: Relevance
“…The Wilk's statistic '˄' was highly significant with value of 1340.221, justifying the calculation of D 2 values. The results are in conformity with the findings of earlier workers (17) who also reported 'V' statistic to be highly significant with value of 2736.30 in their studies on 107 rice genotypes for yield and yield component traits, justifying the need to calculate D 2 values. Similar results were also reported ear-…”
Section: Test With Wilk's Criterion '˄'supporting
confidence: 91%
“…The Wilk's statistic '˄' was highly significant with value of 1340.221, justifying the calculation of D 2 values. The results are in conformity with the findings of earlier workers (17) who also reported 'V' statistic to be highly significant with value of 2736.30 in their studies on 107 rice genotypes for yield and yield component traits, justifying the need to calculate D 2 values. Similar results were also reported ear-…”
Section: Test With Wilk's Criterion '˄'supporting
confidence: 91%
“…Cluster III and cluster VII showed maximum inter-cluster distance (13522.04) followed by cluster III and cluster V (12751.46) which suggested that the genotypes in these clusters had a significant degree of genetic diversity and that crossings between the genotypes in these clusters would produce desirable transgressive segregants. Similar findings were reported by Sudeepthi et al, 2020;Amegan et al, 2020;Sujata et al, 2021. Whereas the lowest inter-cluster distance was noticed between cluster IV and cluster VII (1785.47) followed by cluster I and cluster IV (2107.62), suggesting closeness among the genotypes in these clusters for most of the traits.…”
Section: Shanmugam Et Alsupporting
confidence: 91%
“…Based on clustering pattern Cluster I and II comprised of four and five genotypes respectively, while Cluster III was monogenotypic in nature. Similar studies based on D 2 -statistic was also performed by Sudeepthi et al [15], Singh et al [16], Kumari et al [17], Nirosha et al [18], Sreedhar [19], Singh et al [20] and Devi et al [21]. The clustering pattern showed that genotypes of different geographical areas were clubbed in one group and also the genotypes of same geographical area were grouped into same cluster as well as in different cluster indicating that there was no formal relationship between geographical distribution and genetic diversity.…”
Section: Discussionsupporting
confidence: 79%